Ultrafast high-temperature sintering (UHS) of fine grained α-Al2O3. Issue 13 (October 2021) - Kermani, Milad; Dong, Jian; Biesuz, Mattia; Linx, Yong; Deng, Huaijiu; Sglavo, Vincenzo M.; Reece, Michael J.; Hu, Chunfeng; Grasso, Salvatore
Abstract: Ultrafast High-temperature Sintering (UHS) allows consolidation of ceramics in just a few tens of seconds. The green body is placed within a carbon felt heated by the Joule effect at temperatures up to 3000 °C. Here, we propose a combined experimental and numerical analysis to enable the fabrication of fully dense and fine-grain α-Al2 O3 samples using a multistep computer-controlled current profile. Reference samples processed using a single step current formed cracks at the onset of shrinkage due to their uneven temperature distribution. Fully coupled simulations accounting for electric current, voltage, power, temperature and shrinkage allowed us to improve the experimental setup and to define the current profiles required to UHS highly dense (i.e., relative density > 99 %) 3 mm thick samples with an average grain size of 0.77 μm.